# If find(i) f (0)(ii) f (4)(iii) f (-5)

(i) We have,

Now,

Put t = 0

f(0) = 4(0)2 - 3(0) + 6

= 4(0) - 3(0) + 6

= 0 – 0 + 6

= 6

Hence,

f(0) = 6

(ii) We have,

Now,

Put t = 4

f(4) = 4(4)2 -3(4) + 6

= 4(16) - 3(4) + 6

= 64 – 12 + 6

= 58

Hence,

f(4) = 58

(iii) We have,

Now,

Put t = -5

f(-5)=4(-5)2 - 3(-5) + 6

= 4(25) - 3(-5) + 6

= 100 + 15 + 6

= 121

Hence,

f(0) = 6

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Polynomials29 mins
Polynomials - Zero to Hero42 mins
Genius Quiz | Polynomials40 mins
Zeros and Degrees of a Polynomial41 mins
Genius Quiz | Division of Algebraic Expressions37 mins
Introduction to Polynomials37 mins
Quiz | Imp. Qs. on Algebraic Identities65 mins
Basic understanding of Polynomials37 mins
QUiz on Previous year NTSE Questions45 mins
Methods to find zeroes of a Polynomial-246 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

The zeroes of the polynomial p (x) = x2 + x - 6 are

RS Aggarwal & V Aggarwal - Mathematics

Zero of the polynomial p(x) = 2x + 3 is

RS Aggarwal & V Aggarwal - Mathematics

If find

(i) f (0)

(ii) f (4)

(iii) f (-5)

RS Aggarwal & V Aggarwal - Mathematics

If (x + 1) is a factor of 2x2+ kx, then k =?

RS Aggarwal & V Aggarwal - Mathematics

If (x2+ kx – 3) = (x – 3 ) (x + 1) then k =?

RS Aggarwal & V Aggarwal - Mathematics

The zeroes of the polynomial p (x) = x2 – 3x are

RS Aggarwal & V Aggarwal - Mathematics

The zeroes of the polynomial p (x) = 3x2 – 1 are

RS Aggarwal & V Aggarwal - Mathematics